Zakat, Infaq, and Sedekah (ZIS) Management in Economic Recovery in Makassar Indonesia: A Cross-Cultural Perspective from Turkey and Egypt - Nur Saidy, Emily; Mahsyar, Nun Maziyah; Ashraf, Amal (Institut Agama Islam Negeri Parepare, 2025)
Purpose – This study examines the distribution and effectiveness of ZIS (Zakat, Infak, and Sedekah) funds in revitalizing the mustahik economy in the post-pandemic period. Method – Employing a qualitative phenomenological approach, this research explores the lived experiences of stakeholders while drawing comparisons with the zakat systems implemented in Egypt and Turkey. Findings – The study reveals that, while ZIS distribution in Makassar has positively impacted many beneficiaries, its effectiveness in fostering sustainable economic growth remains constrained by limited funding and a lack of capacity-building programs. Lessons from Egypt and Turkey—such as adopting digital platforms for enhanced transparency and efficiency and fostering institutional collaboration to increase public trust—offer actionable insights for improving the ZIS system in Makassar. Practical Implications – This study provides a global perspective on optimizing ZIS fund utilization to support economic recovery, with practical recommendations for policymakers and zakat institutions. Originality/Value – By adopting a comparative and cross-cultural approach, this study offers unique insights into the distribution and effectiveness of ZIS funds in a post-pandemic context, contributing to the broader discourse on zakat system improvement.